2020
DOI: 10.2147/ott.s277795
|View full text |Cite
|
Sign up to set email alerts
|

<p>Low Levels of SPARC are Associated with Tumor Progression and Poor Prognosis in Human Endometrial Carcinoma</p>

Abstract: Background SPARC (secreted protein acidic and rich in cysteine), also known as osteonectin, BM-40, and 43 K protein, is a matricellular protein associated with various tumor progressions. The aim of this research was to investigate the prognostic value of SPARC in endometrial carcinoma (EC) and its function in cancer cell invasion and metastasis. Methods From both mRNA and protein levels, SPARC expression in normal endometrial tissue and EC tissue, normal endometrial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 56 publications
(57 reference statements)
2
5
0
2
Order By: Relevance
“…Mean OS was 97 months for patients with SPARC expression >14.25% compared to 65 months for patients with expression ≤14.25%. These findings are consistent with the literature, in which there is an association between low SPARC expression and a worse prognosis in endometrial carcinoma ( 76 ), colorectal cancer ( 87 , 88 ), and NSCLC ( 89 ). Furthermore, it is described that, depending on the tumor microenvironment, SPARC can act both as a tumor suppressor and as an oncogene ( 76 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Mean OS was 97 months for patients with SPARC expression >14.25% compared to 65 months for patients with expression ≤14.25%. These findings are consistent with the literature, in which there is an association between low SPARC expression and a worse prognosis in endometrial carcinoma ( 76 ), colorectal cancer ( 87 , 88 ), and NSCLC ( 89 ). Furthermore, it is described that, depending on the tumor microenvironment, SPARC can act both as a tumor suppressor and as an oncogene ( 76 ).…”
Section: Discussionsupporting
confidence: 93%
“…This is a matricellular glycoprotein that directly participates in the ECM remodeling process, regulating processes, such as metalloproteinase secretion and cell-matrix interactions ( 75 ). Recent studies showed that SPARC favored the migration and invasion of endometrial carcinoma cells in vitro and in vivo ( 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…In endometrial cancer (EC), low SPARC expression is related to aggressive EC phenotype and poor prognosis. In addition, down-regulation of SPARC promotes the EMT process and enhances EC cell proliferation and invasion [ 34 ]. The AKAP13 is an anchor protein found in the Rho signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…SPARC is a matricellular glycoprotein that modulates the pathologies associated with tumorigenesis. 28 Jiang et al found that the mRNA and protein expression of SPARC was downregulated in JEG-3 cells compared with HTR-8/SVneo cells. 29 Furthermore, miRNAs in cancer were the primary pathway for DEG enrichment.…”
Section: Discussionmentioning
confidence: 99%